Antidiabetic Activity of Artemisia amygdalina Decne in Streptozotocin Induced Diabetic Rats. (21st May 2014) - Ghazanfar, Khalid; Ganai, Bashir A.; Akbar, Seema; Mubashir, Khan; Dar, Showkat Ahmad; Dar, Mohammad Younis; Tantry, Mudasir A.
Abstract : Artemisia species have been extensively used for the management of diabetes in folklore medicine. The current study was designed to investigate the antidiabetic and antihyperlipidemic effects of Artemisia amygdalina . Petroleum ether, ethyl acetate, methanol, and hydroethanolic extracts of Artemisia amygdalina were tested for their antidiabetic potentials in diabetic rats. The effect of extracts was observed by checking the biochemical, physiological, and histopathological parameters in diabetic rats. The hydroethanolic and methanolic extracts each at doses of 250 and 500 mg/kg b. w significantly reduced glucose levels in diabetic rats. The other biochemical parameters like cholesterol, triglycerides, low density lipoproteins (LDL), serum creatinine, serum glutamate pyruvate transaminase (SGPT), serum glutamate oxaloacetate transaminase (SGOT), and alkaline phosphatise (ALP), were found to be reduced by the hydroethanolic and methanolic extracts. The extracts also showed reduction in the feed and water consumption of diabetic rats when compared with the diabetic control. The histopathological results of treated groups showed the regenerative/protective effect on β -cells of pancreas in diabetic rats. The current study revealed the antidiabetic potential of Artemisia amygdalina being effective in hyperglycemia and that it can effectively protect against other metabolic aberrations caused by diabetes in rats, which seems to validate its therapeutic traditional use.